2014
DOI: 10.1038/ncomms4817
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal adaptation involves rapid expansion of the action potential initiation site

Abstract: Action potential (AP) generation is the key to information-processing in the brain. Although APs are normally initiated in the axonal initial segment, developmental adaptation or prolonged network activity may alter the initiation site geometry thus affecting cell excitability. Here we find that hippocampal dentate granule cells adapt their spiking threshold to the kinetics of the ongoing dendrosomatic excitatory input by expanding the AP-initiation area away from the soma while also decelerating local axonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 54 publications
5
27
0
Order By: Relevance
“…Converging lines of evidence suggest that the AIS is a highly dynamic structure, exhibiting structural plasticity over different timescales ranging from a few hours to several days (7)(8)(9)(10)(11)(12)(13)(29)(30)(31). Various elegant studies used typical triggers of plasticity such as sensory deprivation, optogenetic stimulation, or high-K + -induced depolarization (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Converging lines of evidence suggest that the AIS is a highly dynamic structure, exhibiting structural plasticity over different timescales ranging from a few hours to several days (7)(8)(9)(10)(11)(12)(13)(29)(30)(31). Various elegant studies used typical triggers of plasticity such as sensory deprivation, optogenetic stimulation, or high-K + -induced depolarization (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Long considered to be the trigger zone for AP initiation (28), the AIS was regarded as a static and rigid structure encompassing ion channels anchored to a scaffolding and cytoskeletal protein network. Now, it is recognized that the AIS is a highly dynamic structure, capable of structural and functional plasticity and continuously adapting to changes in neuronal activity (8,12,(29)(30)(31). In 2010, two seminal studies found that changes in neuronal activity could lead to AIS relocation or resizing as a new mechanism of slow homeostatic adaptation (32,33).…”
mentioning
confidence: 99%
“…This inactivation decreases with increasing distance from the soma, due to an electrotonic decrement of the depolarization. Accordingly, neurons overcome the effects of this inactivation and maintain their excitability by transient expansion of AP initiation areas at the AIS (hippocampus, Scott et al, 2014), or by localizing the AIS at a distal location (nucleus laminaris, see above, Kuba et al, 2006). …”
Section: Modulation Via Ionotropic Receptorsmentioning
confidence: 99%
“…First, it may extend the spike initiation site to a wider axonal zone (Scott et al, 2014). But most importantly, it will largely modulate the amplitude of the action potential in the axon upon changes in membrane potential in the cell body (Rama et al, 2015a).…”
Section: Hyperpolarization-induced Ad Facilitation (H-adf)mentioning
confidence: 99%